(3GdJHjGf aj EYQGH GdbQBfs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s
(3ChdgG (B:s
(3Chdg ShQI GdCYQGa , jfbU TjFkG jSjQkG ef ChdgG hChd GdehLhO efg (B: (3jLhR Cf jJYdb HCfRd , hjchf dEHJOGA GdZGjI , hCf jJYdb HeMPha hjchf MGdkG s
(3BNQgG (B:s
(3hCeG GdfGS GdCNjQ , dEbjd (B: (3gh eYWha Ydi Pi GdhShGS , Ci ef TQ (B[ (3GdbHjdJjf (B] (3hbjd gh eYWha Ydi GdLfI gPG BNQ cJGH GdHjGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B46s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JaSjQ (B138) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs